(untitled) (Plant Tissue Culture and Biotechnology, 2013)
Random amplified polymorphic DNA (RAPD) assay was performed to estimate genetic polymorphisim in ten chili cultivars. Out of 12 primers four (OPA11, OPB03, OPB04 and OPB17) showed amplification of genomic DNA and generated 21 distinct score able bands of which 17 (80.95%) were polymorphic. The highest percentage (85.71) polymorphic locus was found in OPB03 while the lowest (66.67) in OPA11. The highest genetic distance was computed between Jamalpur Balujuri and Matal marich with the lowest genetic identity as against the lowest genetic distance between Hajari marich and Balujuri marich. The UPGMA dendogram indicated segregation of ten chili varieties and genotypes into two main clusters. Variety Bogra marich and Matal marich formed cluster 1 and Balujuri marich, Deshi marich, Jamalpuri balujuri, Bindu marich, Syloti, Hajari, Biroli city, and the genotype Ausadhebrara grouped in cluster 2. The result indicates the genetic diversity among the chili cultivars and RAPD marker could be used for improvement of chili varieties. DOI: http://dx.doi.org/10.3329/ptcb.v22i2.14201 Plant Tissue Cult. & Biotech. 22(2): 127-136, 2012 (December)